ASSESSMENT OF SERUM TENASCIN-C AND GROWTH DIFFERENTIATION FACTOR-15 AMONG TYPE 2 DIABETES MELLITUS PATIENTS WITH AND WITHOUT ACUTE CORONARY SYNDROME - Vasanthi, Murugaiyan; Adole, Prashant Shankarrao; Pandit, Vinay Ramakrishna; Vinod, Kolar Vishwanath (Journal of Medical Biochemistry, 2020)
Background: High prevalence of type 2 diabetes mellitus (T2DM) is associated with a higher prevalence of acute coronary syndrome (ACS). Inflammation is one of the important contributors to the pathogenesis and complications of coronary atherosclerotic plaque. Growth Differentiation Factor-15 (GDF-15) and Tenascin-C (TNC) play an important role in the initiation of atherosclerotic plaque as well as its rupture. The aim of the study was to evaluate the association between serum GDF-15, TNC, and the risk of ACS among T2DM patients. Methods: Anthropometric parameters, routine biochemical investigations like liver and renal function tests, lipid profile, and Creatine Kinase-Total (CK-T), Creatine Kinase-MB (CK-MB) were measured in 42 T2DM patients with ACS and 42 T2DM patients. Serum GDF-15 and TNC were measured by Human Sandwich-ELISA kits. Results: Serum GDF-15 and TNC levels were significantly higher in T2DM patients with ACS as compared to T2DM patients. Serum GDF-15 was significantly correlated with waist circumference, diastolic blood pressure,pulse, serum CK-T, and CK-MB. Serum TNC was significantly correlated with the pulse, serum CK-T, CK-MB, high- density lipoprotein-cholesterol, and blood urea nitro gen. Multivariate linear regression analysis showed that waist circumference was independently positively associated with serum GDF-15. Conclusions: T2DM patients with higher serum GDF-15 and TNC levels were at higher risk of acute coronary syndrome independent of other cardiovascular risk factors. Keywords: type 2 diabetes mellitus, acute coronary syndrome, tenascin-C, growth differentiation factor-15.